META-ULTRAMAFIC ROCK FROM THE AUSTKAMPANE AREA OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イシズカ, ヒデオ; スズキ, サトコ; コジマ, ヒデヤス; ISHIZUKA, Hideo; SUZUKI, Satoko; KOJIMA, Hideyasu (National Institute of Polar Research, 1996)
P(論文) In the Austkampane area of the S∅r Rondane Mountains, East Antarctica, a meta-ultramafic rock occurs as a lenticular block enclosed within the host garnet-biotite gneiss of the granulite facies. The rock consists of olivine, orthopyroxene, amphibole, spinel, apatite, ilmenite, magnetite, chalcopyrite and pentlandite. The bulk rock analysis shows an ultramafic composition in a broad sense, but compared with mantle peridotites it is enriched in TiO_2,Al_2O_3,CaO, Nb and Zr, and has a slightly high ratio of FeO^*/MgO. This suggests a slightly differentiated basaltic cumulate as its precursor. After the igneous generation, the rock was incorporated within the original rock of the host gneiss (sedimentary quartzo-feldspathic rock), probably in the form of block-in-matrix, and then both rocks underwent the granulite facies metamorphism. The olivine-spinel geothermometer and Al_2O_3 content of orthopyroxene indicate metamorphic temperatures of about 780-820℃ and 750-800℃, respectively. Similar meta-ultramafic rocks have been reported from the Lützow-Holm Complex, suggesting that the similar association of original rocks such as oceanic lower crusts developed in these two granulite terrains. departmental bulletin paper